The Mitochondrial Citrate Carrier SLC25A1/CIC and the Fundamental Role of Citrate in Cancer, Inflammation and Beyond - Mosaoa, Rami (Biomolecules, 2021)
The mitochondrial citrate/isocitrate carrier, CIC, has been shown to play an important role in a growing list of human diseases. CIC belongs to a large family of nuclear-encoded mitochondrial transporters that serve the fundamental function of allowing the transit of ions and metabolites through the impermeable mitochondrial membrane. Citrate is central to mitochondrial metabolism and respiration and plays fundamental activities in the cytosol, serving as a metabolic substrate, an allosteric enzymatic regulator and, as the source of Acetyl-Coenzyme A, also as an epigenetic modifier. In this review, we highlight the complexity of the mechanisms of action of this transporter, describing its involvement in human diseases and the therapeutic opportunities for targeting its activity in several pathological conditions.